Media Pembelajaran PAI: Definisi, Sejarah, Ragam dan Model Pengembangan - Achmad Faqihuddin (Idarotuna: Jurnal Manajemen Pendidikan Islam, 2024)
Islamic religious education (PAI) learning media plays an important role in conveying religious values and teachings to the younger generation. In this context, the use of various types of media is very important to support teaching effectiveness and attract student interest. This research explores the use of media in PAI, including the integration of technology in learning media. A qualitative approach using the literature review method was used to dig deeper into the definition, history, varieties and development models of PAI learning media. Data analysis using Nvivo 12 software. The literature review is expected to provide an in-depth understanding of the evolution of learning media from traditional to digital methods. The research results show that learning media plays a critical role in facilitating more interactive and immersive religious learning, helping students internalize Islamic values effectively.